TP53 Mutants in the Tower of Babel of Cancer Progression. Issue 6 (14th March 2014) - Bisio, Alessandra; Ciribilli, Yari; Fronza, Gilberto; Inga, Alberto; Monti, Paola; Soussi, Thierry
<x xml:space="preserve">Abstract</x> We review studies investigating TP53 mutations for their effect on the capacity of this protein to act as a transcription factor. We also review recent findings on how TP53 mutants can exhibit gain‐of‐function properties. Somatic as well as germline TP53 mutations are considered, and the possibilities to stratify patients based on the features of P53 mutant proteins are discussed. In the analogy with the Tower of Babel, the different languages stand for the staggering functional heterogeneity of P53 mutants associated with cancer. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>